Gadamer’s legal hermeneutics: complementing legal interpretation theories - Hernández Aguilar, uan Manuel (2019)
Legal interpretation theory has some pending questions thus it is currently dominated by normative positivism which saves itself from any proximity between the interpreter and reductivism schemes that limit judicial activity to the jurisprudential technique. In this stage, Gadamer's hermeneutics appears as a dynamic theory enabled to integrate historical and individual situations. Therefore, we shall analyze the distance in time, effectual history and the fusion of horizons that constitutes the setup for comprehension in order to transit from legal dogmatics theory to one of interpretation and juridical application.